Construction process planning and management an owner's guide to successful projects - Levy, Sidney M. (Butterworth-Heinemann, 2010)
By their very nature, construction projects can create seemingly endless opportunities for conflict. Written by a best selling author with over 40 years of experiences in the construction and general contracting business, Construction Process Planning and Management provides you with the necessary tools to save time and money on your construction project. In this book, Sid Levy provides valuable advice for avoiding or working through the common problems that are a result of the long-term nature of construction projects, failure to select a?project delivery system? appropriate to the project, incomplete drawing and specifications, unrealistic scheduling, poor communication and coordination among participants, and inadequate contract administration. From project genesis, through design development to contractor and contract selection, on to construction oversight, punch list and successful project close-out, this book will point out those pitfalls to avoid and offer practical advice at every step along the way. Administer the general construction process including solicitation of contractor's qualifications (pre-qualify bidders), comparative analysis of bid packages, recommendation for contract award, contract document negotiation and documentation of job change orders. Provide Project Planning and on-site management and coordination of all construction projects. Ensure compliance of building construction rules and regulations and collaborate with chief engineers to monitor quality of construction. Conduct technical/plan review of construction documents and submit written responses identifying required corrections or changes. Design, implement and oversee Company standards for construction policies, practices and processes.
Includes index.
Keywords: Building -- Planning.; Building -- Superintendence.; elektronické knihy; electronic books